The Effect of Right Temporal Lobe Gliomas on Left and Right Hemisphere Neural Processing During Speech Perception and Production Tasks - Yamamoto, Adam Kenji; Sanjuán, Ana; Pope, Rebecca; Parker Jones, Oiwi; Hope, Thomas M. H.; Prejawa, Susan; Oberhuber, Marion; Mancini, Laura; Ekert, Justyna O.; Garjardo-Vidal, Andrea; Creasey, Megan; Yousry, Tarek A.; et al. (Frontiers in Human Neuroscience, 2022)
Using fMRI, we investigated how right temporal lobe gliomas affecting the posterior superior temporal sulcus alter neural processing observed during speech perception and production tasks. Behavioural language testing showed that three pre-operative neurosurgical patients with grade 2, grade 3 or grade 4 tumours had the same pattern of mild language impairment in the domains of object naming and written word comprehension. When matching heard words for semantic relatedness (a speech perception task), these patients showed under-activation in the tumour infiltrated right superior temporal lobe compared to 61 neurotypical participants and 16 patients with tumours that preserved the right postero-superior temporal lobe, with enhanced activation within the (tumour-free) contralateral left superior temporal lobe. In contrast, when correctly naming objects (a speech production task), the patients with right postero-superior temporal lobe tumours showed higher activation than both control groups in the same right postero-superior temporal lobe region that was under-activated during auditory semantic matching. The task dependent pattern of under-activation during the auditory speech task and over-activation during object naming was also observed in eight stroke patients with right hemisphere infarcts that affected the right postero-superior temporal lobe compared to eight stroke patients with right hemisphere infarcts that spared it. These task-specific and site-specific cross-pathology effects highlight the importance of the right temporal lobe for language processing and motivate further study of how right temporal lobe tumours affect language performance and neural reorganisation. These findings may have important implications for surgical management of these patients, as knowledge of the regions showing functional reorganisation may help to avoid their inadvertent damage during neurosurgery.